Figurative Language, Mental Imagery, and Pragmatics. (3rd July 2018) - Carston, Robyn
ABSTRACT: Many people report experiencing mental imagery (visual, auditory, and/or kinetic) when they comprehend verbal metaphors. The question whether imagery is merely an incidental side-effect of processes of metaphor understanding or plays a key role in comprehension remains unresolved, with diametrically opposed views expressed among psychologists, philosophers, and literary theorists. I survey a wide array of evidence (behavioral and neurocognitive) concerning the activation and use of imagery in language processing generally and metaphor processing in particular. I conclude that mental imagery is not an essential component in the comprehension of language, whether literal or metaphorical, but it is often automatically activated in the minds of hearers or readers as a by-product of their linguistic and pragmatic processes. Writers may exploit this fact and enhance the impact of imagery by producing extended and/or creative metaphors, so that, although not essential, imagistic effects can be as significant as propositional cognitive effects.